Chemical Composition of the Essential Oils from Flowers of Senecio vernalis and Senecio platyphyllus var. platyphyllus - Usta, Asu; Ucuncu, Osman; Beyza Cansu, Tayyibe; Terzioglu, Salih; Yayli, Nurettin (Asian Journal of Chemistry, 2010)
Two essential oil samples obtained by hydrodistillation from the flowers of Senecio vernalis Valdst. & Kit., (Asteraceae) and Senecio platyphyllus DC. var. platyphyllus, were analyzed by GC-FID and GCMS. 69 compounds in the oil of S. vernalis, representing 93.4 % and 48 compounds in the oil of S. platyphyllus var. platyphyllus, representing 94.4 %, were identified. The essential oils were rich in monoterpene (53.3 %) and sesquiterpene (76.1 %) hydrocarbons with β-pinene (13.0 %) and (E)-caryophyllene (28.6 %) as the major compounds, respectively.